How are the Cognitive, Affective, and Psychomotor Levels of Primary School Learners Living in Suburban Area of Yogyakarta based on Career Development? - Aprilia Tina Lidyasari; Indriyana Rachmawati; Augusto da Costa; Poh Wanyi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
Career development influences learners’ life in the future and their career selections. The development career of learners at the primary level has an important role to facilitate individuals in planning, understanding, and having clear career identities. This research described the cognitive, affective, and psychomotor levels of Primary School learners living in suburban areas of Yogyakarta based on their career development. The research sample consisted of primary schools in suburban Yogyakarta with 268 learners. The applied sampling technique was convinced sampling. The researchers used the personally developed questionnaire on career development based on Bloom's taxonomy. The questionnaire consisted of cognitive, affective, and psychomotor aspects with expert judgment to validate the questionnaire. The applied technique of analyzing the data was a descriptive technique to explain the cognitive, affective, and psychomotor levels of the primary school learners based on their career development. The applied data type was the frequency to determine the learners' career development levels. The findings showed that 97% of learners had excellent career development. Then, the remaining percentage, 3%, had not developed excellent career development. The evidence was observable in the poor skill to improve achievement and achieve the expected objectives, lack of self-esteem and skills to struggling, and lack of effort to seek help from other friends.